PELAKSANAAN PENGELOLAAN FASILITAS DI KAWASAN TAMAN WISATA ALAM BULUH CINA DI KABUPATEN KAMPAR - Zurika Fitri; Andi Moh Rifiyan Arief (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This research was initiated from the results of researchers' observations regarding the management of facilities in the Taman Wisata Alam Buluh Cina area in Kampar Regency. This study aims to find out about the management of facilities in the Taman Wisata Alam Buluh Cina Area in Kampar Regency. This research is a descriptive research with a qualitative approach. The technique of collecting data was carried out using the methods of observation, documentation, and interviews, while the samples of this study were managers, officers, visitors and the community around the Taman Wisata Alam Buluh Cina. The data in this study were analyzed with the stages of data reduction, data presentation and conclusion drawing. Based on the results of the study, it can be concluded that 1) serious planning for the construction of facilities at the Taman Wisata Alam Buluh Cina but is hindered by the budget 2) the organization is not optimal for each existing facility 3) The implementation is quite good seen from the awareness and attention of the manager and officers at existing facilities 4) have been running quite well, because the supervision and movement of the managers and officers of every facility in the Taman Wisata Alam Buluh Cina is always noticed and supported, but there are some things that are still not good in the implementation of management the facilities. Keywords: Management, Facilities, Nature park